Molecular and Evolutionary Mechanisms of Cuticular Wax for Plant Drought Tolerance - Xue, Dawei; Zhang, Xiaoqin; Lu, Xueli; Chen, Guang; Chen, Zhong-Hua (Frontiers in Plant Science, 2017)
Cuticular wax, the first protective layer of above ground tissues of many plant species, is a key evolutionary innovation in plants. Cuticular wax safeguards the evolution from certain green algae to flowering plants and the diversification of plant taxa during the eras of dry and adverse terrestrial living conditions and global climate changes. Cuticular wax plays significant roles in plant abiotic and biotic stress tolerance and has been implicated in defense mechanisms against excessive ultraviolet radiation, high temperature, bacterial and fungal pathogens, insects, high salinity and low temperature. As one of the most detrimental abiotic stresses, drought limits plant growth and productivity, which poses huge threats to global food security and health of terrestrial ecosystem. The composition, biochemistry, structure, biosynthesis and transport of plant cuticular wax have been reviewed extensively. However, the molecular and evolutionary mechanisms of cuticular wax in plants in response to drought stress are still lacking. In this review, we focus on potential mechanisms, from evolutionary, molecular, and physiological aspects, that control cuticular wax and its roles in plant drought tolerance. We also raise key research questions and propose important directions to be resolved in the future, leading to potential applications of cuticular wax for water use efficiency in agricultural and environmental sustainability.